The blood glucose control levels and influencing factors analysis among diabetes patients in rural areas of Guangxi, China - Chen, Jingfeng; Fu, Guifen; Lei, Xiaoxue; Bai, Chaoqun; Wen, Lina; Zhang, Yanping (Frontiers in Endocrinology, 2025)
ObjectiveDiabetes mellitus is a growing public health concern in China, with the rural areas of Guangxi facing rising prevalence, poor glycemic control, and limited healthcare access despite national efforts to improve diabetes management. This study aimed to evaluate the level of glycated hemoglobin (HbA1c) control and identify associated factors among patients with diabetes in the rural areas of Guangxi, China, to inform strategies for improving diabetes management in these regions.MethodsA multistage stratified random sampling method was employed. In the first stage, five cities (Nanning, Guilin, Hechi, Chongzuo, and Yulin) were randomly selected, each representing a geographical region of Guangxi (central, eastern, southern, western, and northern). In the second stage, three counties were randomly selected from each city, yielding a total of 15 counties. One county-level hospital with a general internal medicine department was selected in each county for patient recruitment. Data on demographic characteristics (e.g., sex, age, household income, type of medical insurance, educational level, and disease duration) were collected, and laboratory testing was conducted to measure HbA1c levels. Glycemic control was defined as an HbA1c level< 7%. Multivariate logistic regression was used to identify factors associated with glycemic control.ResultsA total of 2,178 patients with diabetes were included, of whom 1,204 (55.28%) were men and 974 (44.72%) were women. The mean age was 63.25 ± 12.71 years, and the mean duration of diabetes was 7.96 ± 4.07 years. The overall HbA1c control rate was 22.68%. Logistic regression analysis revealed that older age (OR = 1.026, 95% CI: 1.017–1.036), longer disease duration (OR = 1.137, 95% CI: 1.104–1.171), use of oral hypoglycemic agents (OR = 0.485, 95% CI: 0.377–0.624), insulin therapy (OR = 0.425, 95% CI: 0.388–0.534), and higher educational level (e.g., primary school: (OR = 6.507, 95% CI: 3.076–13.767); junior high school: (OR = 5.557, 95% CI: 2.818–10.955); senior high school: (OR = 2.848, 95% CI: 1.485–5.462); college: (OR = 2.479, 95% CI: 1.285–4.782); and bachelor’s degree: (OR = 1.915, 95% CI: 0.943–3.889), and higher annual per capita household income (OR = 0.626, 95% CI: 0.528–0.830) were significantly associated with glycemic control (p< 0.05).ConclusionThe HbA1c control rate among patients with diabetes in rural Guangxi was relatively low (22.68%). Targeted interventions should focus on patients who are older, have a longer disease duration, are not receiving antidiabetic treatment, have lower educational levels, or have lower income levels to improve glycemic management in rural areas.